Предмет: Алгебра,
автор: angelinabalabai
пожалуйста докажите тождество
Приложения:
Ответы
Автор ответа:
0
упростим левую часть
=х-1)/х² : (х-1)/х -1/х + х/(х-2) - х/(х+2) =(х-1)/х² * х/(х-1) -1/х +х/(х-2) -
- х/(х+2)=1/х -1/х +(х²+2х)-х(х-2))/(х-2)(х+2)= (х²+2х-х²+2х)/(х²-4)=4х/(х²-4)
тождество верно
=х-1)/х² : (х-1)/х -1/х + х/(х-2) - х/(х+2) =(х-1)/х² * х/(х-1) -1/х +х/(х-2) -
- х/(х+2)=1/х -1/х +(х²+2х)-х(х-2))/(х-2)(х+2)= (х²+2х-х²+2х)/(х²-4)=4х/(х²-4)
тождество верно
Похожие вопросы
Предмет: Английский язык,
автор: medonovadaniela3
Предмет: Алгебра,
автор: Svitlana277
Предмет: Математика,
автор: aubibragimov78
Предмет: Математика,
автор: aleksandr9910
Предмет: Математика,
автор: Nayvuvvu